Prognostic factors for VTE and bleeding in hospitalized medical patients: a systematic review and meta-analysis - Darzi, Andrea J; Karam, Samer G; Charide, Rana; Etxeandia-Ikobaltzeta, Itziar; Cushman, Mary; Gould, Michael K; Mbuagbaw, Lawrence; Spencer, Frederick A; Spyropoulos, Alex C; Streiff, Michael B; Woller, Scott; Zakai, Neil A; et al. (Blood, 2020)
There may be many predictors of venous thromboembolism (VTE) and bleeding in hospitalized medical patients, but until now, systematic reviews and assessments of the certainty of the evidence have not been published. We conducted a systematic review to identify prognostic factors for VTE and bleeding in hospitalized medical patients and searched Medline and EMBASE from inception through May 2018. We considered studies that identified potential prognostic factors for VTE and bleeding in hospitalized adult medical patients. Reviewers extracted data in duplicate and independently and assessed the certainty of the evidence using the Grading of Recommendations Assessment, Development, and Evaluation approach. Of 69 410 citations, we included 17 studies in our analysis: 14 that reported on VTE, and 3 that reported on bleeding. For VTE, moderate-certainty evidence showed a probable association with older age; elevated C-reactive protein (CRP), D-dimer, and fibrinogen levels; tachycardia; thrombocytosis; leukocytosis; fever; leg edema; lower Barthel Index (BI) score; immobility; paresis; previous history of VTE; thrombophilia; malignancy; critical illness; and infections. For bleeding, moderate-certainty evidence showed a probable association with older age, sex, anemia, obesity, low hemoglobin, gastroduodenal ulcers, rehospitalization, critical illness, thrombocytopenia, blood dyscrasias, hepatic disease, renal failure, antithrombotic medication, and presence of a central venous catheter. Elevated CRP, a lower BI, a history of malignancy, and elevated heart rate are not included in most VTE risk assessment models. This study informs risk prediction in the management of hospitalized medical patients for VTE and bleeding; it also informs guidelines for VTE prevention and future research.